PENGARUH PERBEDAAN SUHU PENGERINGAN GRANUL (40°C,50°C,60°C) TERHADAP SIFAT FISIK TABLET PARACETAMOL - Agustina Putri Pitarisa Sudarsono; Masithoh Nur; Yahya Febrianto (Jurnal Farmasi & Sains Indonesia, 2021)
The most widely consumed analgesic and antipyretic drug by the community is paracetamol. One of the dosage forms is tablets. The manufacture of tablet preparations must go through various processes, one of which is drying. Things that need to be considered in the drying process include the temperature used for drying. This study aims to determine the difference in drying temperature of the granules on the physical properties of paracetamol tablets. This research uses a comparative type of research, which is to see the effect of differences in granule drying temperature on the physical properties of paracetamol tablets. Tablets were made by wet granulation method which consisted of 3 formulas. The formula used is the same, the only difference is the temperature. The drying temperatures used were 40°C, 50°C, 60°C. Parameters tested for paracetamol tablets include: organoleptic (shape, color, odor), weight uniformity, hardness, friability and disintegration time. The average weight uniformity test results are between 508.65-517 ± 0.48-1.88 mg . The results of the tablet hardness test were between 5.04-7.3 ± 0.29–0.43 kg. The results of the tablet friability test were between 0.48-0.68 ± 0.042-0.13%. The results of the test the time between tablet disintegration was between 4.17-7.07 ± 5.03-12.01 minutes. The results of the statistical test of the granules and the physical properties of the tablets showed that the data were normally distributed with a sign value. > 0.05, in the homogeneity test the data is homogeneous with the sign value. > 0.05. The results of the ANOVA One-Way test obtained sign results. <0.05, which means that there is a significant difference between the formulas.